Prototype Layanan Izin Pemanfaatan Ruang Menggunakan Service Oriented Enterprise Architecture Framework - Desak Putu Juniati (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
When people make a discussion about license registration process, they usually give focus only on the integrated service that put all the included services together in one place. While in fact, on the other hand, there are vital aspects that are not yet handled properly regarding the information presentation served to people in need. The people served in this discussion are those who need the information about land availability and its appropriate use related to the regulation established. The objective of this research is to create the prototype for the service of land using permit (Izin Pemanfaatan Ruang), especially for tourist accommodation business, which the registration service is carried out in The License Registration Office of Karangasem Regency. This prototype consists of two main services that are the service presented in front office and the service presented in back office. The front office service prototype is presenting the service on the information about spatial and attribute data related to the land ownership and land use blocking regulation. The information about the land ownership is given by conducting an integrated service with The National Land Office of Karangasem Regency, while the information about the land use blocking regulation is given by conducting an integrated service with The Development Planning Office of Karangasem Regency. The research is carried out by using the approach of Service Oriented Enterprise Architecture Framework (SOEAF), which integrates Service Oriented Architecture (SOA) into the framework of Enterprise Architecture. The integration is conducted by using the extension of Zachman framework which adding a new column named service column consisting contextual level, conceptual level, logical level and physical level. The result of this research is a prototype for the service of land using permit for tourist accommodation that has interoperability data so as to provide land availability for users.